2016
DOI: 10.1109/tbcas.2014.2371695
|View full text |Cite
|
Sign up to set email alerts
|

An On-Chip Multi-Voltage Power Converter With Leakage Current Prevention Using 0.18 um High-Voltage CMOS Process

Abstract: In this paper, we present an on-chip multi-voltage power converter incorporating of a quad-voltage timing-control rectifier and regulators to produce ±12 V and ±1.8 V simultaneously through inductive powering. The power converter achieves a PCE of 77.3% with the delivery of more than 100 mW to the implant. The proposed rectifier adopts a two-phase start-up scheme and mixed-voltage gate controller to avoid substrate leakage current. This current cannot be prevented by the conventional dynamic substrate biasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Substituting the self-body bias circuit with an adaptive body bias circuit, Cheng et al were able to achieve PCE up to ~92% and VCE up to 96%, the highest values reported to date. A quad-voltage rectifier suitable for both low and high compliance voltage has been proposed in [17], [56]. The proposed architecture consists of both HV and LV halfwave active rectifiers with a mixed-voltage gate controller to avoid substrate leakage current at high compliance voltage.…”
Section: B Active and Synchronous Rectificationmentioning
confidence: 99%
“…Substituting the self-body bias circuit with an adaptive body bias circuit, Cheng et al were able to achieve PCE up to ~92% and VCE up to 96%, the highest values reported to date. A quad-voltage rectifier suitable for both low and high compliance voltage has been proposed in [17], [56]. The proposed architecture consists of both HV and LV halfwave active rectifiers with a mixed-voltage gate controller to avoid substrate leakage current at high compliance voltage.…”
Section: B Active and Synchronous Rectificationmentioning
confidence: 99%
“…The core of the implant is a mixed-signal, multi-voltage SoC performing 160-channel current stimulation with high compliance voltage, 16-channel recording, and 48-channel bio-impedance characterization with fully integrated power/data telemetry. Improved upon [30], a quad-voltage power converter generates four different voltages to power the implant, with added capability of adjusting the supply voltages for the stimulators (± 6/8/10/12 V) to accommodate various bio-impedances. A quasi full-duplex data transceiver links the SoC and the rendezvous device at 2 Mb/s.…”
Section: System Overviewmentioning
confidence: 99%
“…A class-E power amplifier in PTT is used to deliver the power wirelessly to PTR through an inductive link. The PTR is based on the fully integrated multi-voltage power converter developed by the authors [35]. The PTR can not only provide the DC power required by the TX, serializer, and recorder of the implantable module, but also support high DC voltage if functional electrical stimulation (FES) is to be embedded in the implant.…”
Section: The Proposed System Architecture For Large-scale Wirelementioning
confidence: 99%
“…The PTR can not only provide the DC power required by the TX, serializer, and recorder of the implantable module, but also support high DC voltage if functional electrical stimulation (FES) is to be embedded in the implant. Details of the wireless power link can be found in [35] In this work, we focus on the realization of the wireless gigabit data link, where both 60 GHz TX and RX are critical in the realization of a high data rate transmission. The TX and RX are modified from our previous design that is originally targeted at wire-line communication [36].…”
Section: The Proposed System Architecture For Large-scale Wirelementioning
confidence: 99%